2022
DOI: 10.3390/ijerph19074148
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds for Fibromyalgia-like Symptoms: A Narrative Review and Future Perspectives

Abstract: Fibromyalgia (FM) is a prevalent, chronic condition without a cure or reliable therapy. The etiopathogenesis of this syndrome is ambiguous, which has heightened the challenge of discovering treatments to minimize patients’ painful symptoms. FM is characterized by diffuse musculoskeletal pain usually accompanied by functional pain syndromes, such as fatigue, sleep disturbances, cognitive difficulties, and mood issues. Currently available treatment options for FM are limited. Recent studies have suggested a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…These include capsaicin, ginger, and turmeric, among other bioactive compounds. However, human studies examining supplementation with these compounds are limited [ 63 ]. Due to muscle weakness associated with FM, some studies have also examined the therapeutic potential of creatine supplementation.…”
Section: Minerals and Supplements In Fibromyalgiamentioning
confidence: 99%
“…These include capsaicin, ginger, and turmeric, among other bioactive compounds. However, human studies examining supplementation with these compounds are limited [ 63 ]. Due to muscle weakness associated with FM, some studies have also examined the therapeutic potential of creatine supplementation.…”
Section: Minerals and Supplements In Fibromyalgiamentioning
confidence: 99%
“…The effect of ginger rhizome has been studied in an experimental mouse model of FM, and this trial provides evidence that the daily consumption of GR complements the anti-nociceptive effect of paracetamol in mice, improves other cognitive disturbances associated with pain, and lowers the inflammatory state generated in an experimental FM model [ 140 ]. Likewise, animal studies have demonstrated that curcumin has anti-inflammatory and antioxidant potential in FM-like symptoms by suppressing numerous cell-signaling pathways involved in inflammation [ 141 ]. A very limited number of human studies have been conducted to evaluate curcumin’s therapeutic potential in FM patients.…”
Section: Experimental Evidence From Human Studies On Herbs and Spices...mentioning
confidence: 99%
“…Coenzyme Q10, for example, has shown potential in reducing fatigue, a common symptom in CFS/ME and fibromyalgia. The anti-inflammatory properties of curcumin may also contribute to managing pain in individuals with fibromyalgia (20).…”
Section: Treatment Optionsmentioning
confidence: 99%